2007
DOI: 10.1007/s12011-007-8018-2
|View full text |Cite
|
Sign up to set email alerts
|

Serum Selenium Concentrations Correlate Significantly with Inflammatory Biomarker High-sensitive CRP Levels in Hungarian Gestational Diabetic and Healthy Pregnant Women at Mid-pregnancy

Abstract: Selenium is an essential trace element and a component of various enzymes with antioxidant functions. High-sensitive C-reactive protein (hsCRP) is an early indicator of increased lipid peroxidation. The serum selenium concentration, lipid parameters, and hsCRP values of gestational diabetic pregnant women (GD), control pregnant women (CP), and healthy nonpregnant controls (HC) were compared. Blood was taken between the 24th and the 28th week of pregnancy when the oral glucose tolerance test was performed. Sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 19 publications
(28 reference statements)
3
46
0
Order By: Relevance
“…Our results indicating a significant inverse relationship between serum selenium and hsCRP are in agreement with literature [16,17,29]. We found also significant negative correlation between serum selenium and HOMA-IR.…”
Section: Discussionsupporting
confidence: 93%
“…Our results indicating a significant inverse relationship between serum selenium and hsCRP are in agreement with literature [16,17,29]. We found also significant negative correlation between serum selenium and HOMA-IR.…”
Section: Discussionsupporting
confidence: 93%
“…[233][234][235][236] Lower plasma/serum Se levels have also been found in gestational diabetic pregnancies with respect to normal pregnancies. 237,238 Conversely, other works have found high Se status in patients with diabetes, or did not observe any significant differences. 239,240 Finally, in some cases the difference in Se status was limited to specific sub-groups such as males 241 or patients with a disease duration r2 years.…”
Section: Diabetesmentioning
confidence: 85%
“…Many epidemiological studies demonstrated that serum Se levels were lower in diabetic patients than in healthy individuals. [17][18][19] The atrophy and degeneration of pancreatic islets have also been reported in patients with the Se-deficiency syndrome, Keshan disease.…”
Section: )mentioning
confidence: 93%